2006
DOI: 10.1007/s00520-006-0070-5
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the malnutrition screening tool as an effective predictor of nutritional risk in oncology outpatients receiving chemotherapy

Abstract: The MST has acceptable relative validity, inter-rater reliability, sensitivity, and specificity to identify chemotherapy outpatients at risk of malnutrition and, hence, is an acceptable nutrition screening tool in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
101
3
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(109 citation statements)
references
References 24 publications
3
101
3
2
Order By: Relevance
“…In a study by Bauer (2002), PG-SGA is suggested for cancer patients and shows that the resulting score of this questionnaire is related to weight loss in the previous 6 months and hospitalization (Akbari, 2008). In a similar study on 71 patients using PG-SGA, the results demonstrated a sensitivity of 98% and a specificity of 82% (Bauer et al, 2002;Isenring et al, 2006;Witowich, 2008). Isenring et al (2003) also examined the PG-SGA scores on the basis of weight loss over the previous 6 months, BMI and quality of life percent and also the changes in QOL after 4 weeks of radiation therapy.…”
Section: Nutritional Assessment Of Cancer Patients In Tehran Iranmentioning
confidence: 83%
See 1 more Smart Citation
“…In a study by Bauer (2002), PG-SGA is suggested for cancer patients and shows that the resulting score of this questionnaire is related to weight loss in the previous 6 months and hospitalization (Akbari, 2008). In a similar study on 71 patients using PG-SGA, the results demonstrated a sensitivity of 98% and a specificity of 82% (Bauer et al, 2002;Isenring et al, 2006;Witowich, 2008). Isenring et al (2003) also examined the PG-SGA scores on the basis of weight loss over the previous 6 months, BMI and quality of life percent and also the changes in QOL after 4 weeks of radiation therapy.…”
Section: Nutritional Assessment Of Cancer Patients In Tehran Iranmentioning
confidence: 83%
“…The present study makes use of PG-SGA (Bauer et al, 2002;Isenring et al, 2006) which is considered as the best standard questionnaire used in oncologic patient's nutritional status (Ferguson et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…From the nutrition assessment tool of PG-SGA, the result we got indicated that BMI alone cannot be a reliable indicator of nutritional status of an individual in cancer patients. Previous studies in cancer patient groups also highlighted the limitations of using BMI as the sole measure of nutritional status (Desbrow et al, 2005;Isenring et al, 2006).…”
Section: Co-relation Between Pg-sga Score and Bmimentioning
confidence: 99%
“…26,27 The MST is a simple 3-question tool that asks respondents to report the presence and quantity of any recent weight loss and its relation to decreased appetite, with possible scores ranging from 0 to 6. A score of !2 indicates the patient is at risk of malnutrition.…”
Section: Nutritional Statusmentioning
confidence: 99%